Huber-Braun neuron dynamics - Vera-Ávila, V.; Jaimes Reátegui, R.; Sevilla Escoboza, R.; Huerta-Cuéllar, G.; García-López, J.; López Mancilla, D.; Camacho Castillo, L.; Castañeda Hernández, C.; Pisarchik, A. (Acta Universitaria, 2013)
We study a physiologically realistic implementation of internal stochasticity in a four dimensional Hodgkin-Huxley (HH) type model of cold receptors. We show that in a deterministically tonic-firing regime, changing the parameters can drive the neuron into a state of complex bursting behavior. An explanation of the mechanism behind this effect is given in terms of a bifurcation diagram of inter-spike interval (ISI) as the temperature and external current are altered.